The Influence of Embodied Cultural Capital on the Retention and Matriculation Adults Entering College - Pamela Hampton-Garland (Adult Education Research Conference, 2015)
The purpose of this paper is to highlight the challenges of non-traditional students entering college and to offer suggestions on research that addresses these challenges. Embodied cultural capital is the core of who we are and how we define ourselves. It is through this capital that an individual identifies their authentic self. Embodied cultural capital is derived from one’s life-long investment in education from all sources including community, family and schooling.
Keywords: embodied cultural capital; cultural capital; non-traditional students